1976
DOI: 10.1159/000122480
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Puberty-Controlling Function of the Mediocortical Amygdala in the Immature Female Rat

Abstract: The puberty-controlling function of the mediocortical amygdala in immature female rats was investigated by lesioning this region at different ages and by studying the effects on the onset of spontaneous and experimentally-induced precocious puberty. At 21 days of age, bilateral lesions in the anterior mediocortical amygdala (AMCA) caused precocious puberty and enhanced the puberty-accelerating effect of bilateral lesions produced simultaneously in the medial preoptic area (MPA). Similar lesions, ineffective on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
12
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 4 publications
2
12
0
Order By: Relevance
“…This further indicates that the limbic system and in particular the amygdala when damaged bilat erally prevents the impairment of gonadal function produced by over crowding. These results concur with studies indicating precocious puberty [Elwers and Critchlow, 1960;Docke et a!., 1976] and enhanced LH secretion [Eleftheriou and Zolovick, 1967] following amygdalar ablation. The amygdala, therefore, may be a subcortical nuclear site responsible for the adrenal and gonadal effects arising from grouping or increased population density.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This further indicates that the limbic system and in particular the amygdala when damaged bilat erally prevents the impairment of gonadal function produced by over crowding. These results concur with studies indicating precocious puberty [Elwers and Critchlow, 1960;Docke et a!., 1976] and enhanced LH secretion [Eleftheriou and Zolovick, 1967] following amygdalar ablation. The amygdala, therefore, may be a subcortical nuclear site responsible for the adrenal and gonadal effects arising from grouping or increased population density.…”
Section: Discussionsupporting
confidence: 92%
“…Other studies have suggested that the limbic system and in particular the amygdala is involved in the regulation of these functions [Endroczi et al, 1959;Bovard and G loor, 1961;Knigge, 1961;M andell et al, 1963], Bilateral lesions of the amygdala induce precocious puberty in female rats and result in elevated serum lutein izing hormone (LH) in deermice of both sexes [Elwers and Critchlow, I960;Eleftheriou and Zolovick, 1967;Docke et al, 1976], Conversely daily electrical stimulation of the cortico-medial nucleus of the amygdala has been shown to decrease LH production in the normal cycling rat and to delay puberty in the immature rat [Bar-Sela and Critchlow, 1966;Ellendorf et al. 1973].…”
mentioning
confidence: 99%
“…These divergent results may reflect that Nor-man and Spies’ study created lesions at 10–13 months of age, after amygdala development is almost complete (Payne et al, 2010; Chareyron et al, 2012), compared to approximately one month of age in the current study, when the amygdala has the greatest volume increase and shows substantial morphological changes (Payne et al, 2010; Chareyron et al, 2012). These different effects of amygdala lesions on pubertal timing based on lesion timing are consistent with data in female rats showing that lesions of the anterior MeA at 15 days of age delayed pubertal onset, lesions at 21 days of age resulted in earlier pubertal onset, and lesions at 26 days of age had no effect on pubertal onset (Döcke, 1974; Döcke et al, 1976, 1980). It is also possible that different environmental conditions may have produced the differing results between the effects of juvenile lesions and our neonatal lesions.…”
Section: Discussionsupporting
confidence: 87%
“…In female rats, amygdala lesions alter the timing of pubertal onset with the direction of the effect varying with the developmental timing of the lesion. Bilateral lesions of the anterior medial amygdala in 15-day-old female rats delay pubertal onset, lesions of 21-day-old rats result in earlier pubertal onset, but lesions at 26 days of age do not affect pubertal onset (Döcke, 1974; Döcke et al, 1976, 1980). In individually-housed female rhesus monkeys, lesions of the entire amygdala at 10–13 months of age, after the amygdala is fully developed (Payne et al, 2010), do not influence menarchal age (Norman and Spies, 1981).…”
mentioning
confidence: 99%
“…Such an hypothesis is in keeping with the observation that an increased amount of oestrogen is required in ovariectomized rats to reduce LH levels as adulthood is attained (Steele & Weisz, 1974). The concept of such an inhibition is not new, and there is much evidence to suggest that the amygdala may be involved in such a role (Critchlow & Bar-Sela, 1967;Docke, 1976). Should such a neural or humoral inhibition exist the present data indicate that it would be specific for LH but not FSH releasing mechanisms, and furthermore, that in the male or the androgentreated female either the sensitivity of the LH-secreting system to inhibition is greater or the inhibitory signal is more potent than in the female.…”
Section: Discussionmentioning
confidence: 62%